Efektivitas Mediasi dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Sangatta Berdasarkan Perma No 1 Tahun 2016 tentang Mediasi - Nabilah Khoirunnisa; Irma Suriyani; Amsari Damanik (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the effectiveness of mediation in resolving divorce cases at the Sangatta Religious Court under Supreme Court Regulation (Perma) No. 1 of 2016 on Mediation Procedures in Courts. It employs a socio-legal method combining the statute approach and the sociological approach. Primary data were drawn from interviews with mediating judges and the court registrar, secondary data from statutory regulations, and tertiary data from legal dictionaries. The analysis is built on Soerjono Soekanto's theory of legal effectiveness, which identifies five factors the substance of the law, law enforcers, facilities and infrastructure, society, and legal culture as indicators of successful law enforcement. The findings show that mediation has been carried out in accordance with Perma No. 1 of 2016, yet its success rate remains low: of 2,351 divorce cases mediated between 2022 and 2024, only 212 cases (9.02%) reached a peaceful settlement. This low effectiveness is attributable to the limited number of certified mediators, the absence of non-judge mediators, a caseload disproportionate to the time allotted for mediation, and weak good faith among the parties. The study recommends strengthening mediator capacity and numbers, involving certified non-judge mediators, and providing legal education to the public as strategic steps to reduce the divorce rate in Sangatta.